2009
DOI: 10.1093/carcin/bgp081
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced genomic instabilities caused by deregulated microtubule dynamics and chromosome segregation: a perspective from genetic studies in mice

Abstract: Aneuploidy is defined as numerical abnormalities of chromosomes and is frequently (>90%) present in solid tumors. In general, tumor cells become increasingly aneuploid with tumor progression. It has been proposed that enhanced genomic instability at least contributes significantly to, if not requires, tumor progression. Two major modes for genomic instability are microsatellite instability (MIN) and chromosome instability (CIN). MIN is associated with DNA-level defects (e.g. mismatch repair defects), and CIN i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 61 publications
(92 reference statements)
4
76
0
Order By: Relevance
“…Insufficient mitotic arrest results in abnormal cell cycle progression and decreased cell proliferation via chromosome abnormality. 12,[17][18][19] Hence, we wanted to examine the long-term consequences of MTBP downmodulation on cellular behavior and chromosome aneuploidy. We first examined the effect of MTBP downmodulation on cell growth using colony outgrowth assays (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Insufficient mitotic arrest results in abnormal cell cycle progression and decreased cell proliferation via chromosome abnormality. 12,[17][18][19] Hence, we wanted to examine the long-term consequences of MTBP downmodulation on cellular behavior and chromosome aneuploidy. We first examined the effect of MTBP downmodulation on cell growth using colony outgrowth assays (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%
“…Both decreased and increased levels of mitotic checkpoint proteins cause a similar cellular response, including improper mitotic progression, chromosome aneuploidy, senescence, and tumor development via impaired and overactive mitotic checkpoint activities, respectively. 12,18,22,23 Therefore, proteins involved in the mitotic checkpoint cannot be simply categorized as either oncogenes or tumor suppressors. Mice null for Mad1, Mad2, BubR1, Bub1, and Bub3 show early embryonic lethal phenotypes because of chromosome missegregation.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the effects of genomic instability and resulting aneuploidy on carcinogenesis, various mouse models have been developed, mainly by targeting mitotic or other cell cycle regulators (Foijer, Draviam, & Sorger, 2008; Rao, Yamada, Yao, & Dai, 2009; Ricke, van Ree, & van Deursen, 2008; Schvartzman, Sotillo, & Benezra, 2010). Shugoshin‐1 (Sgo1) protects cohesin proteins and centrosome integrity (Salic, Waters, & Mitchison, 2004; Schöckel, Möckel, Mayer, Boos, & Stemmann, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that TRIP13 is a novel component of the spindle assembly checkpoint (SAC) pathway (14)(15)(16)(17), which is crucial for the accurate distribution of duplicated chromosomes (18). Defects in the SAC pathway induce failure in chromosome separation and result in aneuploidy, which eventually leads to cellular apoptosis or transformation (19). TRIP13 was also reported to promote nonhomologous end-joining, and its overexpression resulted in cellular transformation and resistance to chemotherapeutic agents, indicating that aberrant expression of TRIP13 may be associated with tumor progression (20).…”
Section: Introductionmentioning
confidence: 99%